2017
DOI: 10.3389/fpsyg.2016.02048
|View full text |Cite
|
Sign up to set email alerts
|

Symptomatic Remission and Counterfactual Reasoning in Schizophrenia

Abstract: Counterfactual thinking (CFT) is a type of conditional reasoning involving mental representations of alternatives to past factual events that previous preliminary research has suggested to be impaired in schizophrenia. However, despite the potential impact of these deficits on the functional outcome of these patients, studies examining the role of CFT in this disorder are still few in number. The present study aimed to extent previous results by evaluating CFT in the largest sample to date of schizophrenia pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 60 publications
2
17
1
Order By: Relevance
“…The relatively small size of the group, the use of only a survey and self-reported scale for data collection, cross-sectional study design so could not determinate the effects of abuse processes on CFT (e.g., processes related to early years of marriage or later years) are the important limitations of the study. In addition, it should be noted that the total score of 2.5/4 found in non-victims is not consistent with the normative pattern proposed by Hooker et al and is consistent with the low CIT scores in the healthy group of Albacete et al's study 14,24 . On the other hand, we demonstrated that IPV exposure is also severe in women at the high socioeconomic level and is associated with the decrease in CFT ability, which is a sign of cortical-subcortical functions.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…The relatively small size of the group, the use of only a survey and self-reported scale for data collection, cross-sectional study design so could not determinate the effects of abuse processes on CFT (e.g., processes related to early years of marriage or later years) are the important limitations of the study. In addition, it should be noted that the total score of 2.5/4 found in non-victims is not consistent with the normative pattern proposed by Hooker et al and is consistent with the low CIT scores in the healthy group of Albacete et al's study 14,24 . On the other hand, we demonstrated that IPV exposure is also severe in women at the high socioeconomic level and is associated with the decrease in CFT ability, which is a sign of cortical-subcortical functions.…”
Section: Discussioncontrasting
confidence: 55%
“…Counterfactual inference is a part of CFT. There are many studies that had been linked counterfactual thinking problems and defects in counterfactual inference ability with psychopathologies including depression [10][11][12][13] , schizophrenia 14,15 , gambling behavior 13,16 , posttraumatic stress disorder-other trauma-related conditions 9,13,17 and obsessive-compulsive disorder 18 , which are also related to corticalsubcortical region dysfunctions. On the other hand, research on the problems which are subclinical but could have an effect on cognition and CFT are still scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Twelve studies (41%) probed the generation of counterfactual thoughts related to a negative real-life [ 14 16 , 22 27 ] or a fictional event [ 9 , 23 , 25 , 28 , 29 ]. Ten studies (34%) administered the Counterfactual Inference Test (CIT) [ 22 ] to investigate the ability to use CFT to make causal inferences in fictional social scenarios [ 12 , 14 16 , 22 , 24 , 28 31 ]. Six works (21%) used the Counterfactual Thinking for Negative Events Scale [ 32 , 33 ] or similar questionnaires [ 34 – 37 ] investigating the content (e.g., upward/downward) and the affective aspects of CFT.…”
Section: Resultsmentioning
confidence: 99%
“…Individuals who implement an effective CFT are expected to behave anticipating future regret. Finally, two studies (7%) probed the “causal order effect” [ 41 ], meaning the tendency to choose the first event of a sequence as the most decisive for the final negative outcome [ 9 , 28 ]. Finally, two studies (7%) investigated the influence of CFT on the automatic activation of behavioral intentions using the sequential priming paradigm [ 10 , 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, the implementation of corrective behaviours (Step 3) appears to be intact in these patients [ 23 ]. With regard to these findings, however, it should be noted that although deficits in CFT activation (Step 1) have been widely reported not only in patients with schizophrenia [ 24 26 ] but in their unaffected first-degree relatives [ 27 ], research into the activation of behavioural intentions (Step 2) is still scarce [ 28 ].…”
Section: Introductionmentioning
confidence: 99%